Gerindra Party's Political Narrative on TikTok During the 2024 Presidential & Vice Presidential Election Campaign Period - Amani, Husnaeni Fauziah; Windrati, Nila Kusuma; Maulida, Gita Khuzaimah (Riwayat: Educational Journal of History and Humanities, 2025)
TikTok has become a social media platform experiencing rapid user growth in Indonesia. During the 2024 Presidential Election campaign, TikTok became a crucial platform for creating political narratives, especially for young voters. Gerindra is a political party that actively used TikTok, with 35 posts during the campaign period. Fifteen posts from Gerindra's TikTok account received more than one million views. This study examines the political narratives used by the Gerindra Party during the 2024 Presidential and Vice Presidential Election campaign on TikTok. This research is qualitative, using Barthes's semiotics as its analytical tool. From 35 content posts on Gerindra's TikTok during the campaign period, researchers categorised them into six categories. These categories are: Prabowo attending campaign events, content in image format, Prabowo speaks at forums, broadcasts of presidential candidate debates, Prabowo's humanistic side, and Prabowo's informal activities. Within each category, researchers selected posts with high impressions. Analysis of the TikTok posts shows that the Gerindra Party used symbols that support Prabowo Subianto's political narrative in its election campaign. The political narrative created by the Gerindra Party TikTok account focuses less on the programs that presidential candidate Prabowo will implement and more on Prabowo's brand image.